Mutual funds' cost persistence - Artur A. Trzebiński (Financial Internet Quarterly, 2022)
The research aimed to check whether investment fund managers maintain costs similarly from period to period. The research verified the hypothesis that managers maintain costs in the subsequent periods at a similar level. The study used a method based on contingency tables which are used to analyse the persistence of performance. In this study, we replaced performance with costs, assuming that managers also control these values. Costs were defined as: (1) total costs, (2) total costs minus management fees and (3) active management costs (expressed as the active expense ratio). Based on the results obtained, it should be stated that managers maintain costs at a similar level from period to period in the case of the split using the median. On the other hand, the results indicate that the costs were not maintained at a similar level in subsequent periods when broken down into quartiles. Considering the detailed results for funds divided into quartiles, it is clearly visible that most managers keep the costs close to the average value. Less frequently, costs from period to period are changed to be allocated to the extreme quartiles.
Keywords: G11; G14; G23; 330; cost persistence; mutual funds; total cost; active management